2022
DOI: 10.1002/slct.202203305
|View full text |Cite
|
Sign up to set email alerts
|

Probing N‐Alkoxy Effects in Domino Reactions of α‐Bromoacetamide Derivatives Towards Functionalized γ‐Lactams

Abstract: The main objective of the present work is to better delineate the positive impact of N‐alkoxy versus N‐alkyl moieties in domino reactions. The key role of the metallic counterion of the basic reagent via a templating effect has been established, giving an insight over the superiority of N‐alkoxy α‐bromoacetamides compared to their N‐alkyl analogues. The former demonstrated enhanced reactivity and efficiency, thus requiring milder conditions and leading to a wider scope of γ‐lactams in good to excellent yields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These findings demonstrated that the electron-donating groups -OBn or other -OR groups could remarkably improve the reaction efficiency. 20 Considering the higher reactivity of non-substituted α-bromohydroxamates than that of α-substituted α-bromohydroxamates and previous reports, 13,15a a plausible mechanism of the reaction process is proposed in Scheme 1. α-Halohydroxamate was reacted with NaI to yield the corresponding iodide. Subsequently, the resulting carbanion of β-keto nitrile under basic conditions could attack α-iodohydroxamate via an S N 2 process to afford the intermediate I, which subsequently underwent intramolecular nucleophilic addition to produce the cyclized product II, followed by intramolecular dehydration under acidic conditions to furnish the product 3aa.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These findings demonstrated that the electron-donating groups -OBn or other -OR groups could remarkably improve the reaction efficiency. 20 Considering the higher reactivity of non-substituted α-bromohydroxamates than that of α-substituted α-bromohydroxamates and previous reports, 13,15a a plausible mechanism of the reaction process is proposed in Scheme 1. α-Halohydroxamate was reacted with NaI to yield the corresponding iodide. Subsequently, the resulting carbanion of β-keto nitrile under basic conditions could attack α-iodohydroxamate via an S N 2 process to afford the intermediate I, which subsequently underwent intramolecular nucleophilic addition to produce the cyclized product II, followed by intramolecular dehydration under acidic conditions to furnish the product 3aa.…”
Section: Resultsmentioning
confidence: 90%
“…These findings demonstrated that the electron-donating groups –OBn or other –OR groups could remarkably improve the reaction efficiency. 20 Considering the higher reactivity of non-substituted α-bromohydroxamates than that of α-substituted α-bromohydroxamates and previous reports, 13,15 a a plausible mechanism of the reaction process is proposed in Scheme 1. α-Halohydroxamate was reacted with NaI to yield the corresponding iodide.…”
Section: Resultsmentioning
confidence: 96%
“…The use of N-methylacrylamide led to no conversion, confirming the need for the alkoxy moiety onto the nitrogen atom. 5 We then turned our attention toward enals and enones 2 in reaction with acrylamide 1b as depicted in Scheme 2, and The impact of steric effects was confirmed when enals carrying cycloalkyl substituents on the β position were engaged, only with moderate to acceptable yields ranging from 20 to 55% being obtained depending on the size of the ring. 12 Functionalized enals bearing alkene or protected heteroatoms were also nicely tolerated forming 3l−3n in 60−80% yield.…”
mentioning
confidence: 99%
“…Hamada and co-workers published in 2012 a well-designed iminium-based enantioselective aza-Michael/Michael sequence starting from N -alkoxyacrylamides (Scheme b) . This organocatalytic reaction implied equipping the acrylamides 1 with an N -alkoxy moiety (R 1 = OR 1 ) to increase aza-nucleophilicity and a β-ester (R″ = CO 2 R) to cause umpolung of the α-center into an electrophilic site. On reaction with cinnamaldehyde derivatives or cyclic enones, these custom [1,3]-N,Cα-dipolar acrylamides gave, after subsequent NaBH 4 reduction in MeOH of the aldehyde function, the desired densely functionalized γ-lactams 4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation